Astra : lost in space. 3, Secrets - Shinohara, Kenta, 1974- (Shonen Jump manga., 2018)
After their nightmare on Shummoor, the group arrives at the third planet on their journey, Arispade. The planet has plenty of food, water and sunshine, making it just like a tropical paradise and the perfect place to relax. Even the lone wolf of the group, Ulgar, starts to open up! That is, until he suddenly pulls out a gun and threatens to kill Luca! Could Ulgar be the traitor the group has been looking for?!